Assessing and Mapping Erosion Risk for Velikoy Sub-watershed within Coruh River Basin in Turkey - Mustafa Tufekcioglu; Mehmet Yavuz; Can Vatandaslar; Musa Dinc; Ahmet Duman; Aydin Tufekcioglu (Doğal Afetler ve Çevre Dergisi, 2018)
Vegetation on earth surface is the integral part of the world ecosystems in functioning for varying spatial and temporal scales. Along with other benefits, land-use as a forest can dramatically reduce the soil erosion and water pollution by protecting the soil surface from erosive effects of rainfall. The objective of this study was to determine rill/interrill (surface) erosion risk by using the RUSLE equation for Velikoy sub-watershed (417 km2) which has rich forest-resources within the Coruh River Basin located at northeastern Turkey. Land use and cover (C factor), rainfall and runoff (R factor), soil erodibility (K factor), slope length and steepness (LS factor), and management support practice (P factor) were identified as the sub-factors for the RUSLE equation and were multiplied to estimate soil loss by rill/interrill erosion. Results showed that the mean surface soil erosion from the sub-watershed was around 3.9 t ha-1 yr-1. Of the total study area, 8.2% was estimated as the areas of high and very high risk for the potential surface soil erosion that also indicates prioritization for the implementation of the erosion conservation measures.